Secrets of the Hospital Underbelly: Patterns of Abundance of Antimicrobial Resistance Genes in Hospital Wastewater Vary by Specific Antimicrobial and Bacterial Family - Perry, Meghan R.; Lepper, Hannah C.; McNally, Luke; Wee, Bryan A.; Munk, Patrick; Warr, Amanda; Moore, Barbara; Kalima, Pota; Philip, Carol; de Roda Husman, Ana Maria; Aarestrup, Frank M.; Woolhouse, Mark E. J.; et al. (Frontiers in Microbiology, 2021)
Background Hospital wastewater is a major source of antimicrobial resistance (AMR) outflow into the environment. This study uses metagenomics to study how hospital clinical activity impacts antimicrobial resistance genes (ARGs) abundances in hospital wastewater. Methods Sewage was collected over a 24-hour period from multiple wastewater collection points representing different specialties within a tertiary hospital site and simultaneously from community sewage works. High throughput shotgun sequencing was performed using Illumina HiSeq4000. ARG abundances were correlated to hospital antimicrobial usage (AMU), data on clinical activity and resistance prevalence in clinical isolates. Results Microbiota and ARG composition varied between collection points and overall ARG abundance was higher in hospital wastewater than in community influent. ARG and microbiota compositions were correlated (Procrustes analysis, P=0.014). Total antimicrobial usage was not associated with higher ARG abundance in wastewater. However, there was a small positive association between resistance genes and antimicrobial usage matched to ARG phenotype (IRR 1.11, CI 1.06 - 1.16, P<0.001). Furthermore, analysing carbapenem and vancomycin resistance separately indicated that counts of ARGs to these antimicrobials were positively associated with their increased usage (carbapenem rate ratio (RR) 1.91, 95% confidence intervals (CI) 1.01 – 3.72, P=0.07, and vancomycin RR 10.25, CI 2.32 – 49.10, P<0.01). Overall, ARG abundance within hospital wastewater did not reflect resistance patterns in clinical isolates from concurrent hospital inpatients. However, for clinical isolates of the family Enterococcaceae and Staphylococcaceae, there was a positive relationship with wastewater ARG abundance (odds ratio (OR) 1.62, CI 1.33 – 2.00, P<0.001, and OR 1.65, CI 1.21 – 2.30, P=0.006 respectively). Conclusions We found that the relationship between hospital wastewater ARGs and antimicrobial usage or clinical isolate resistance varies by specific antimicrobial and bacterial family studied. One explanation we consider is that relationships observed from multiple departments within a single hospital site will be detectable only for ARGs against parenteral antimicrobials uniquely used in the hospital setting. Our work highlights that using metagenomics to identify the full range of ARGs in hospital wastewater is a useful surveillance tool to monitor hospital ARG carriage and outflow and guide environmental policy on AMR.